FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI KADER JUMANTIK DALAM MELAKSANAKAN PEMBERANTASAN SARANG NYAMUK DI KECAMATAN DENPASAR SELATAN - CahyadI, I Made Oka; Purnama, Sang Gede (ARCHIVE OF COMMUNITY HEALTH; Vol 7 No 2 (2020): Desember 2020DO - 10.24843/ACH.2020.v07.i02.p03, 2020)
ABSTRACT South Denpasar District is a sub-district with the highest DHF cases in Denpasar City. In the last 3 years the development of cases of Dengue Hemorrhagic Fever (DHF) in South Denpasar Subdistrict, which is 1,074 cases in 2016, 290 cases in 2017 and 33 cases in 2018. The formation of the Jumantiks by the Denpasar City Government is expected to reduce the cases of dengue fever in Denpasar city. This study aims to determine the participation characteristics of Jumantiks cadres and the factors that influence the participation of Jumantiks cadres in implementing PSN in South Denpasar District. The design of this study was cross sectional with a sample size were 105 cadres with the sampling technique using an exhaustive sampling method where all existing populations were used as samples so as not to cause perceptions of discrimination. The results showed that 96 respondents (91.4%) belonged to active participation and 9 respondents (8.6%) were classified as less active. Factors that influence the participation of Jumantik cadres include education, income, availability of facilities, family support, years of work, age, knowledge and supervision. While the factors of giving awards and community support did not affect the participation of Jumantik cadres in implementing PSN in South Denpasar District.